Deviance & deviants: a sociological approach - Thompson, William E. (Wiley-Blackwell, 2017)
"Often misconstrued as a synonym for depravity, deviance reflects more profoundly on the socially-constructed norms it is defined in opposition to than on the individual behaviors it is used to describe. This groundbreaking new textbook provides an engaging, sociologically-informed examination of how deviance is defined and what it means to be classed a deviant. Featuring an analytical through-line assessing the role of media in crafting and perpetuating definitions of deviance, the book examines an array of sexual, mental, and criminal deviances, as well as addressing those that are often overlooked, such as elite deviance, cyberdeviance, and deviant occupations. The authors interrogate pseudoscientific explanations for deviant behavior debunking many of the myths associated with deviance. With questions to measure specific learning outcomes, a rolling glossary of key terms, and insights from people who have themselves been labeled as deviant, Deviance and Deviants will inform and enlighten students interested in better understanding the nuances of society's relationship with deviance"--